The pH-dependent and enzymatic release of cytarabine from hydrophilic polymer conjugates - Pola, R; Janoušková, O; Etrych, T (Physiological research, 2016)
Cytarabine is one of the most efficient drugs in the treatment of hematological malignancies. In this work, we describe the synthesis and characterization of two different polymer conjugates of cytarabine that were designed for the controlled release of cytarabine within the leukemia cells. Reactive copolymers of N-(2-hydroxypropyl)methacrylamide (HPMA) and 3-(3-methacrylamidopropa-noyl)thiazolidine-2-thione) or 3-(Nmethacryloylglycyl-phenylalanylleucylglycyl)thiazolidine-2-thione were used in the study as reactive polymer precursors for reaction with cytarabine. The enzymatic release of cytarabine from the conjugate containing a GFLG spacer utilizing cathepsin B was verified. In addition to enzymolysis, the pH-dependent hydrolysis of cytarabine from both copolymers was also confirmed. Approximately 40 % and 20 % of the drug was released by spontaneous hydrolysis at pH 7.4 within 72 h from the polymer conjugates with the GFLG and beta-Ala spacers, respectively. At pH 6.0, the spontaneous hydrolysis slowed down, and less than 10 % of the drug was liberated within 72 h. The results of the cytotoxicity evaluation of the polymer conjugates in vitro against various cell lines showed that the cytotoxicity of the polymer conjugates is approximately three times lower in comparison to free cytarabine.
Keywords: polymery; cytarabin; nosiče léků; Drug Carriers; Humans; Methacrylates; Polymers; Antimetabolites, Antineoplastic; lidé; Cell Line, Tumor; methakryláty; protinádorové antimetabolity; nádorové buněčné linie; Cytarabine